Molecular Markers for the DNA fingerprinting of Paphiopedilum dayanum and Paphiopedilum lowii, two endangered slipper orchids - Kenneth Francis Rodrigues; Vijay Kumar Subbiah; Zaleha A. Aziz; M. A. Latip (Springer Verlag, 2009)
Molecular markers were developed for the DNA fingerprinting of Paphiopedilum dayanum and Paphiopedilum lowii, two endangered slipper orchids, endemic to Borneo. A total of eight and fourteen genomic loci containing putative microsatellites were converted into ten species specific molecular markers for multi-locus genetic fingerprinting of P. dayanum and P. lowii, respectively.